School Starting Age and the Impact on School Admission - Julio Cáceres-Delpiano; Eugenio Giolito (Institute of Labor Economics (IZA), 2023)
This study employs Chilean administrative data to investigate the impact of School Starting Age (SSA) on the characteristics of students' initial enrolled schools. Employing minimum age requirements and an RD-design to mitigate endogeneity concerns, we identify benefits linked to commencing school at a later age. Our findings demonstrate that children starting school at an older age enroll in institutions with higher average scores in standardized tests and interact with older peers whose parents have higher education levels. Furthermore, they display a heightened likelihood of entering schools employing academic selection methods, a greater proportion of fulltime teachers, and a larger percentage of instructors with a 4-year college degree.The analysis by level of education of the parents and gender reveals that most of our results are driven by parents with lower levels of education and girls.
Keywords: A21; I24; I25; I28; 330; Latin America; Chile; school starting age; schools' characteristics